2020
DOI: 10.3892/ijmm.2020.4547
|View full text |Cite|
|
Sign up to set email alerts
|

Long noncoding RNA SNHG14 promotes�the�aggressiveness of retinoblastoma by sponging microRNA‑124 and thereby upregulating STAT3

Abstract: A long noncoding RNA called small nucleolar RNA host gene 14 (SNHG14) has been validated as a key regulator of cellular processes in multiple types of human cancer. However, to the best of our knowledge, the expression status and specific roles of SNHG14 in retinoblastoma (RB) have not been studied. The aims of the present study were to determine the expression status of SNHG14 in RB, assess the effects of SNHG14 on malignant characteristics of RB cells and investigate the mechanisms of action of SNHG14 in RB.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…Recent studies indicated that SNHG14 functioned as a tumor promoter by sponging different miRNAs in a series of cancers, such as retinoblastoma, pancreatic ductal adenocarcinoma, and osteosarcoma (Hou and Mao, 2020;Sun et al, 2020;Xie et al, 2020). SNHG14 was uncovered to be highly expressed in ischemic stroke, and the inhibition of SNHG14 mitigated neuron inflammatory damage (Qi et al, 2017;Zhong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that SNHG14 functioned as a tumor promoter by sponging different miRNAs in a series of cancers, such as retinoblastoma, pancreatic ductal adenocarcinoma, and osteosarcoma (Hou and Mao, 2020;Sun et al, 2020;Xie et al, 2020). SNHG14 was uncovered to be highly expressed in ischemic stroke, and the inhibition of SNHG14 mitigated neuron inflammatory damage (Qi et al, 2017;Zhong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…SNHG14 overexpression was involved in the malignant progress in RB patients. And, patients with higher expression of SNHG14 exhibited shorter overall survival than those with lower expression of SNHG14 (Sun et al, 2020). Decreasing SNHG14 inhibited RB cell proliferation, migration, and invasion, promoted apoptosis in vitro, and suppressed tumor growth in mouse tumor xenograft models (Sun et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, the expression levels of certain lncRNAs, such as SNHG5 and tectonic family member 2, have been discovered to be upregulated in SCI ( 25 , 26 ). Therefore, therapies that target lncRNAs may hold promise for the treatment of SCI ( 27 ). SNHG14 is located within the Prader-Willi critical region and extends into the region of the ubiquitin protein ligase E3A gene, whose deficiency in brain cells in children was revealed to contribute to neurogenetic disorders ( 28 ).…”
Section: Discussionmentioning
confidence: 99%